Dietary intake and physical lifestyle of residential college students in Universiti Kebangsaan Malaysia - Nik Hairi Omar,; Tang, Pei Ling; Lim, Seng Joe; Komate Ramaya, (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia, 2015)
A survey regarding dietary intake and physical lifestyle among Residential College Students was conducted in Universiti Kebangsaan Malaysia (UKM). The objectives of study were to determine and evaluate student’s dietary intake and physical lifestyle in the campus which focus to Ungku Omar Residential College, one of the 12 Residential Colleges in UKM. This study was used experimental research design where 100 students (10 percent of population) have been selected randomly through their quotas of race and gender. The results show that the dietary intake of macronutrient carbohydrate, fat and protein taken by the majority of the students (≥50%) have been met the satisfied level as suggested by The Malaysian Food Pyramid Guideline. However, 35-57 percents of student were consuming high calories and high fat food diet. Based on the data obtained, there are relationship between the pattern of students’ dietary intake and quality of services and food inside the campus. According to the students’ perception, the food outlets (cafeteria) in campus were providingbalanced diet, but the quality and safety of food and services were still unsatisfied. The result also found that the students were practicing an active lifestyle with moderate outdoor exercise during their campus life. We concluded that the students in Ungku Omar’s Residential College are practicing healthy campus lifestyle with a satisfied level of balanced dietary intake and physical lifestyle. However, further improvements and attention on students’ dietary intake, especially vegetables, fruits, calories and fat intake are necessary. Therefore, the cafeteria and Residential College administration need to monitor and improve the status of dietary and physical lifestyle among students periodically through a constant survey.